Table of Content - -, (Journal of agricultural, environmental and veterinary sciences, 2025)
Table of Content:• Camel treatment through ages: A comparative study in Veterinary MedicineProf. Mohamed Mostafa Seif• Review: Curry leaves and their role in naturally preserving meat proteins and meat productsAsst-Prof. Lina S. Mohammed ,Asst-Prof. Alia Z. Hashem , Asst-Prof. Mohammed A. Salman• Investigation of Listeria monocytogenes in Meat of Broilers at The Northwestern Region of SyriaAlaa Aldin Sobaia Alrahil , Prof. Fouad Hamad Al-Daoud• Nanotechnology and its Role in the Advancement of Horticultural Crops: A Scientific ArticleAsst-Prof. Fatin H. Al-Dulaimi  , Prof. Mohammed A. H. Al-Najjar , Prof. Sukeyna. A. Aliwy, Prof. Wasen F. Fadel• Spatial Suitability of Harvesting Floodwater in The King Suleiman bin Abdelaziz’s Royal Reserve by Using GIS "Wadi Tawarn as a Model"Ms. Norah Mashaan Aid,  Dr. Ummhani Idris Ahmed• Evaluation of pollination of date palm trees of the Halawi variety with pollen of the Canary  and green Ghanamy date palms on productivity and chemical components of fruitsProf. Muntaha Abdul Zahra Ati, Asst-Prof. Abdul Samad A.Abdullah• Sustainable Valorization of Olive Oil By-products for Food Applications: Mini ReviewMs. Ohoud Hussin Almasaudi, Dr. Asmahan Azhari ,Prof. Mohamed Gadallah Elsayed Gadallah
Keywords: Journal of Agricultural, Environmental and Veterinary Sciences